2020
DOI: 10.1155/2020/5918587
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Restores the Balance of Th17/Treg Cells via Aryl Hydrocarbon Receptor to Attenuate Colitis

Abstract: As one of the ligands of aryl hydrocarbon receptor (AhR), baicalein, isolated from Scutellaria baicalensis Georgi, has been proved to exert potential therapeutic effects on ulcerative colitis (UC), but its therapeutic mechanism remains obscure. Authentically, ulcerative colitis can be alleviated by regulating the differentiation of naïve CD4+ T cells via AhR activation. So, our study planned to prove the hypothesis that baicalein protected mice against UC by regulating the balance of Th17/Treg cells via AhR ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 53 publications
2
30
0
Order By: Relevance
“…CH-223191 administration avoided the amelioration of symptoms of colitis associated with baicalein and abrogated the baicalein-dependent restoration in the balance between Th17 and Treg cells. Moreover, CH-223191 prevented the anti-inflammatory effect of AHR activation by precluding the decrease of the proinflammatory cytokines tumor necrosis factor ɑ (TNF-ɑ) and interleukins 6 (Il-6) and 17 (Il-17) and the increase of anti-inflammatory cytokines (transforming growth factor—TGF-β and IL-10) [ 71 ].…”
Section: Pharmacological Effects Of the Antagonists Of Ahr Canonical Pathwaymentioning
confidence: 99%
“…CH-223191 administration avoided the amelioration of symptoms of colitis associated with baicalein and abrogated the baicalein-dependent restoration in the balance between Th17 and Treg cells. Moreover, CH-223191 prevented the anti-inflammatory effect of AHR activation by precluding the decrease of the proinflammatory cytokines tumor necrosis factor ɑ (TNF-ɑ) and interleukins 6 (Il-6) and 17 (Il-17) and the increase of anti-inflammatory cytokines (transforming growth factor—TGF-β and IL-10) [ 71 ].…”
Section: Pharmacological Effects Of the Antagonists Of Ahr Canonical Pathwaymentioning
confidence: 99%
“…Baicalein is the main ingredient of Coptidis rhizoma. Studies have suggested its anti-inflammatory effect and discovered that it could improve the inflammatory state of UC and the control drugs [39][40][41]. e effect of baicalein is similar to that of the reference drug sulfasalazine and comparable to wogonin [42,43].…”
Section: Discussionmentioning
confidence: 87%
“…In addition, Tregs can also promote the polarization of macrophages from an inflammatory phenotype to an anti-inflammatory phenotype ( Lui et al, 2020 ). Restoring the balance between Th17 and Tregs can reduce colitis ( Liu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%